The Relationship between Economic Status and Child Health: Evidence from the United States - Condliffe, Simon; Link, Charles R (American Economic Review, 2008)
Anne Case et al. (2002), using cross-sectional data, found a positive relationship between children's health and income, with income's protective effect increasing with age. Janet Currie and Mark Stabile (2003), using a panel of Canadian children, found that low- and high-SES children respond similarly to health shocks, but the low-SES children are subject to more shocks as they age. Our study examines this relationship using panel data for US children. We find some support for the latter result of Currie and Stabile, but also evidence that low- and high-SES children respond differently to specific health shocks. (JEL D31, I12, J13)